The Role and the Current Status of IFRS in the Completion of National Accounting Rules – Evidence from Spain. (4th May 2017) - Mora, Araceli
Abstract: The way Spain adapted the legislation to the Accounting Directives as well as a brief analysis of the Spanish standard setting process is followed by a description of the influence of International Financial Reporting Standards (IFRS) is the Spanish legislation and the different stakeholders' position on IFRS. We show and explain why the local General Accepted Accounting Principles (GAAP) are clearly inspired by IFRS principles, even for Small- and Medium-Size entities, while at the same time there is no direct application of IFRS and no mention of IFRS as a complementary source of interpretation. We explain the influence of different stakeholders in the standard setting process and highlight the mostly positive attitude towards IFRS principles. We also show the major differences between the IFRS and local GAAP.